Temperature effects on leaf growth of cassava (Manihot esculenta Crantz) in controlled environments - Akparobi, S.; Togun, A.; Ekanayake, I.J. (2000)
The leaf is the site of photosynthetic activities and crop productivity is controlled by the sizes and efficiency of leaves. Leaf development in cassava can be dependent on genetic makeup of the plant and it is sensitive to temperature. The aim of this study was to quantify the relationships between varying low temperature regimes (32/22°C, 25/2 0°C, 20/15°C, and 15/10°C, day/night temperature respectively) and development of leaf area in eight cassava clones (TMS 30555, TMS 91934, TMS 4(2) 1425, TMS 30001, TMS 30572, Danduala, Danwaru and TME 1). Results showed that leaf initiation took about 10,13 and 17 days at 32/22°C, 25/20°C, and 20/15°C respectively, while none of the clone had leaf initiation at 15/10°C. The young leaves completely opened 6, 10 and 13 days after leaf initiation under 32/22°C, 25/20°C and 20/15°C respectively. The optimum temperature for leaf expansion was 32/22°C. The leaf expansion continued for 20, 27 and 33 days after appearance at 32/22°C, 25/20°C, and 20/15°C respectively. The leaves were significantly different (P < 0.05) in mature leaf sizes, and plants at 32/22°C had the largest leaf sizes and also highest total leaf area when compared to other temperature regimes. Significant clonal differences in time of leaf initiation, time for leaf to unfold, days to full expansion, mature leaf sizes and total leaf area were observed. TME 1 and TMS 30572 had the shortest time to leaf initiation and time to unfold. Also, TMS 30572 and TME 1 had larger leaf areas than the other clones in temperature combinations. The total biomass accumulation and growth rates were temperature sensitive and closely related to leaf growth among the clones tested. The results showed that total biological yield of cassava are dependent on the plant’s photosynthetic capacity. Early leaf initiation and short time to leaf unfolding may be favorable attributes for improving cassava tolerance to low temperatures.